Enhanced supercapacitive performance of the CoFe2O4/CoFe2S4 composite nanoflake array induced by surface sulfidation. (9th August 2019) - Gao, Mengjiao; Le, Kai; Du, Wenjing; Wang, Zhou; Wang, Fenglong; Liu, Wei; Liu, Jiurong
Abstract : The CoFe2 O4 /CoFe2 S4 composite nanoflake array was prepared by surface sulfidation and exhibited outstanding electrochemical performance. Abstract : Herein, a nanoflake array composed of CoFe2 O4 and CoFe2 S4 was in situ assembled on nickel foam (CFS-10/NF) via a simple surface modification by sulfidation; the composition and structure of this array were confirmed by various techniques such as transmission electron microscopy and X-ray diffraction. When applied as an additive-free electrode material, the 3D CFS-10/NF sample exhibited an outstanding capacitance property (4.6 F cm −2 at 1 mA cm −2 ), good rate capability and stable cycling performance. The asymmetric supercapacitor device with CFS-10/NF as an anode and activated carbon as a cathode showed superior performance with the high areal capacitance of 190.5 mF cm −2 and the energy density of 19.8 W h kg −1 . Moreover, the sample exhibited good cycling stability with 100% capacitance retention after 3000 cycles. Due to the rich redox reaction and high electrical conductivity boosted by the well-designed composition as well as large specific surface area and a short ion transportation path attributed to its nanoflake structure, the composite material demonstrates a promising prospect in energy storage applications.